IMPLEMENTASI KEBIJAKAN VAKSINASI COVID-19 DI KOTA SURABAYA - Muhammad Akbar Asyafin; Diaz Virdani; Kiki Darma kasih; Lukman Arif (Journal Publicuho, 2021)
The purpose of this study is to describe implementation of COVID-19 vaccination policy, to find supporting and inhibitings factors or efforts to overcomes them in Surabaya city. Theoretical approach used is the George C. Edward III policy implementation approach. Thiss research use qualiitative methods with a descriptives approach. Data collection carried out through observatiion and interviews. Analysis data techniques in this reseacrh consisted of data collections, data condensations, data presentations, and drawing conclusions according to Miles-Huberman model. Results show that  implementation of COVID-19 vaccination policy in the City of Surabaya in fact found a number of problems in implementation of the COVID-19 vaccination on Surabaya, including realization  vaccines to targets far from the target set, the reluctance of potential vaccine recipients to inform the cause of their absence to health facility officers, less the active target group of potential vaccine recipients to come according to the set schedule. Another cause that is no less important is the lack of synchronization of data on potential vaccine recipients obtained by health facilities as administrators, because some of the data entered are potential vaccine recipients who are survivors, some were even founds to have vaccinated elsewhere. So, socialization from the local government regarding implementation of COVID-19 vaccination policy in Surabaya City important and provides education. Therefore, researchers suggest that there be improvements and synchronization of data on potential vaccine recipients, so that vaccine recipients are well monitored and integrated.